2011
DOI: 10.2175/106143010x12681059117256
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐treatment of Industrial Wastewater Polluted with Lead Using Adsorbents and Ultrafiltration or Microfiltration Membranes

Abstract: This work investigated the use of ultrafiltration (UF) or microfiltration (MF) membranes combined with natural minerals for the pre-treatment of wastewater containing high amounts of lead. The effects of initial lead concentration, solution pH, membrane pore size, mineral type and concentration and mineral -metal contact time were investigated. Lead removal accomplished by the UF system was higher in wastewater compared to that obtained in aqueous solutions and this was attributed to the formation of insoluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 70 publications
0
3
0
2
Order By: Relevance
“…However, previous experimental work has shown that bentonite exhibits higher selectivity for Pb compared to zeolite. [38] This means that the positive impact of minerals on biomass activity is not only associated with the amount of metals adsorbed on them, but also to other reasons such as the potential aggregation between mineral and sludge particles. In the case of zinc, the adsorption capacity of minerals coincides with the decreasing order of sludge inhibition (bentonite > zeolite).…”
Section: Monascus Rubermentioning
confidence: 99%
“…However, previous experimental work has shown that bentonite exhibits higher selectivity for Pb compared to zeolite. [38] This means that the positive impact of minerals on biomass activity is not only associated with the amount of metals adsorbed on them, but also to other reasons such as the potential aggregation between mineral and sludge particles. In the case of zinc, the adsorption capacity of minerals coincides with the decreasing order of sludge inhibition (bentonite > zeolite).…”
Section: Monascus Rubermentioning
confidence: 99%
“…Pb 2+ is an important source of pollution in wastewater with a wide range of sources. Non-ferrous metal mining, lead storage batteries, electronics, metal electroplating, steel manufacturing and other industries will produce a large amount of lead-containing wastewater (Chen et al, 2021;Katsou et al, 2011). Pb 2+ is not degradable and can exist in the environment for a long time, causing the Pb 2+ content in water and soil to exceed the standard (Liu et al, 2013), and causing serious harm to human health through the food chain (EI-Eswed et al, 2017;Yuan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The application of UF or MF membranes combined with natural minerals for the pre-treatment of wastewater containing high amounts of lead was investigated (Katsou et al, 2011b). At pH 5-6, the dominant removal mechanism was precipitation/complexation, while mineral adsorption enhanced lead removal.…”
mentioning
confidence: 99%